Modelling of Cu, Ni, Zn, Mn and Pb transport from soil to seedlings of coniferous and leafy trees - Baltrėnaitė, Edita; Butkus, Donatas (Journal of Environmental Engineering and Landscape Management, 2007)
Transport of trace metals (TMs) from the soil to a plant involves chemical, physical and biological processes (such as diffusion, adsorption, absorption, growth of a plant, transpiration rate, etc.) in the soil, the soil rhizosphere and in the plant itself. Because of the complexity of these processes and external factors (e.g. weather conditions, biotic factors, type of substrate, etc.) the processes are difficult to describe by mathematical formulas. Modelling of TMs transport to plants is even more complex than that of organic contaminants because, contrary to organic contaminants, TMs are essential for plant growth, metabolism, enzyme activity, etc. The octanol‐water partitioning coefficient for TMs in plants gives only limited information about their accumulation, therefore, other coefficients, such as bioconcentration and translocation coefficients, must be incorporated. The aim of this work was to simulate transport of TMs (Zn, Pb, Cu, Ni and Mn) from the soil to tree seedlings by adapting a generalized model of contaminant uptake by plants. The model applied for transport of TMs from the soil to trees was created by Hung and Muckay. When employing this model for modelling transport of TMs from the soil, amended with industrial sewage sludge, to seedlings of coniferous and leafy trees, some adjustments were made by evaluating the equilibrium partitioning coefficient of TMs between octanol and water (Kow); by introducing the equilibrium partitioning coefficient of TMs in the soil and water (K d ), which depends on the soil pH and the amount of organic matter; by introducing the coefficient (KT) of TMs solubility in water as well as by introducing corrective coefficients. When using the Hung and Muckay's model of the transport of trace metals from the soil to tree seedlings, the results of modelling differed approximately by 6 % in leaves, 5 % in the stem and 8 % in roots as compared with those of measurements.Cu, Ni, Zn, Mn ir Pb pernašos iš dirvožemio į spygliuočių ir lapuočių medžių sodinukus modeliavimasSantrauka. Sunkiųjų metalų (SM) pernaša iš dirvožemio į augalą apima cheminių, fizikinių ir biologinių procesų (tokių, kaip difuzija, adsorbcija, absorbcija, augalo augimas, transpiracijos greitis ir kt.), vykstančių dirvožemyje, rizosferos zonoje ir pačiame augale. Dėl šių procesų sudėtingumo ir išorinių veiksnių poveikio (pvz., klimato sąlygos, biotiniais veiksniai, substrato rūšis ir kt. juos sudėtinga aprašyti matematinėmis išraiškomis. Metalų pernašos į augalus modeliavimas yra dar sudėtingesnis negu organinių teršalų, nes, kitaip nei organiniai teršalai, sunkieji metalai yra svarbūs augalų augimui, medžiagų apykaitai, fermentų veiklai ir kt. Sunkiųjų metalų pasiskirstymo tarp oktanolio ir vandens koeficientas suteikia nedaug informacijos apie sunkiųjų metalų kaupimosi augaluose pobūdį, todėl būtina įtraukti papildomus koeficientus, pvz., biologinio pasisavinimo ir translokacijos koeficientus. Šio darbo tikslas buvo sumodeliuoti sunkiųjų metalų (Zn, Pb, Cu, Ni ir Mn) pernašą iš dirvožemio į medžio sodinukus, pritaikant Hung ir Muckay sukurtą teršalų pernašos į augalus modelį. Pritaikant modelį sunkiųjų metalų pernašai iš dirvožemio su paskleistu pramoniniu nuotekų dumblu į spygliuočių ir lapuočių medžių sodinukus atlikta keletas korekcijų, įvertinant sunkiųjų metalų pusiausvyros pasiskirstymo tarp oktanolio ir vandens koeficientą (Kow), sunkiųjų metalų pusiausvyros tarp dirvožemio ir vandens koeficientą (Kd), kuris priklauso nuo dirvožemio pH ir organinės medžiagos kiekio, ir įtraukiant sunkiųjų metalų tirpumo vandenyje koeficientą (KT), taip pat pataisos koeficientus. Pritaikius Hung ir Muckay modelį sunkiųjų metalų pernašai iš dirvožemio į medžių sodinukus, modeliavimo rezultatai nuo matavimo rezultatų skyrėsi apie 6 % lapuose, 5 % kamiene ir 8 % šaknyse.Reikšminiai žodžiai: sunkieji metalai, modeliavimas, pernaša, sodinukai, pušis, beržas, juodalksnis.Моделирование переноса Cu, Ni, Zn, Mn и Pb из почвы в caженцы хвойных и лиственных деревьевРезюме. Перенос тяжелых металлов из почвы в дерево сопровождается многими физическими, химическими и биологическими процессами (такими, как диффузия, адсорбция, абсорбция, рост дерева, скорость транспирации и др.), прoисходящими в почве, зоне ризосферы и самом дереве. Эти процессы математически трудно описать из-за их сложности и влияния внешних факторов (например, климатических условий, биотических факторов, вида субстрата и др.). Моделирование переноса металлов из почвы в дерево является более сложным, чем переноса органических загрязнителей, поскольку они иначе влияют на рост растений, кругооборот веществ, действие ферментов и др. Например, распределение тяжелых металлов между октиловым спиртом и водой дает неполную информацию о накоплении тяжелых металлов в растениях, поэтому необходимо ввести дополнительные коэффициенты, например, коэффициенты биологического освоения и транслокации. Целью настоящей работы было применение модели Ганга и Маккея (Нung and Muckay), cозданной для определения переноса загрязняющих веществ в растения, для моделирования переноса тяжелых металлов из почвы с добавленным в нее промышленным илом в саженцы хвойных и лиственных деревьев. Существующая модель откорректирована путем введения коэффициентов равновесия тяжелых металлов между октиловым спиртом и водой (Kow), между почвой и водой (Kd), зависящих от кислотности почвы и количества органического вещества; коэффициента, определяющего разбавляемую часть тяжелых металлов (KT), а также некоторых поправочных коэффициентов. После применения экспериментально установленных коэффициeнтов и поправок в модели Ганга и Маккея оказалось, что результаты моделирования отличались от результатов измерения на 6 % в листъях, на 5 % – в стволе и на 6 % – в корнях саженцев деревьев.Ключевые слова: тяжелые металлы, моделирование, перенос, саженцы, сосна, береза, черная ольха.First Published Online: 14 Oct 2010